2013
DOI: 10.1190/tle32040386.1
|View full text |Cite
|
Sign up to set email alerts
|

Geomechanical and geometric seismic attributes in an interpretation workflow for characterization of unconventional reservoirs

Abstract: Conventional seismic attributes often provide satisfactory results, especially in the characterization of conventional reservoirs such as sandstones. This is not so evident with more compact, low-permeability, and apparently uniform reservoirs, which comprise substantial reserves in amounts unthinkable a few decades ago, and whose development seemed almost impossible until very recently. Unconventional reservoirs considered in this article are located in a predominantly Jurassic-Cretaceous rifted depositional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Overlaid on the TOC display is the most-positive-curvature attribute, using a transparency. Although the seismic signature of some of the bigger and more coherent lineaments (marked with magenta arrows) confirms them as faults, many of the consistent and weaker lineaments (indicated with orange arrows) have been interpreted as eolian events associated with megadunes (Cardoso et al, 2012;Trinchero et al, 2013).…”
Section: Characterization Of the Vaca Muerta Formationmentioning
confidence: 99%
“…Overlaid on the TOC display is the most-positive-curvature attribute, using a transparency. Although the seismic signature of some of the bigger and more coherent lineaments (marked with magenta arrows) confirms them as faults, many of the consistent and weaker lineaments (indicated with orange arrows) have been interpreted as eolian events associated with megadunes (Cardoso et al, 2012;Trinchero et al, 2013).…”
Section: Characterization Of the Vaca Muerta Formationmentioning
confidence: 99%
“…Overlaid on the TOC display is the most-positive curvature attribute using transparency. While the seismic signature of some of the bigger and coherent lineaments as marked with magenta arrows confirms them as faults, many of the consistent and weaker lineaments indicated with orange arrows have been interpreted as Aeolian events associated with mega dunes (Cardoso et al, 2012;Trinchero et al, 2013). The characteristics of the sedimentary events that deposited the basal part of the VM sequence have been studied based on the geology of the area as well as the well data.…”
Section: Claudio Sylwanmentioning
confidence: 99%
“…Other recent studies have shown ways of combining conventional seismic attributes with geometric and geomechanical attributes to characterize unconventional shale environments (Trinchero et al, 2013). Attribute integration methods can range from simple corendering techniques (Gupta et al, 2011) to complex neural networks-based property modeling approaches (Clifford and Aminzadeh, 2011).…”
Section: Introductionmentioning
confidence: 99%